INVESTIGATING THE EFFICACY OF NURSE-DRIVEN INTERVENTIONS IN MITIGATING THE WORLDWIDE DEFICIT OF NURSING PERSONNEL - Nashmeyah Hmadian Al Rashedy, Amnah Menwer Fayed Alrashidi, Sabahah Saad Dabis Alazmi, Amal Mubarak Nafea Al Rashidi , Amani Mazyad Almutairi , Maram Abdullah Almutairi, Saleh Mohammed Alklywy,; Abdullah Bader Almutairi, Ahmad Noman Alsaleh, Fahad Khulaif Almutairi, Mahdi Suhaim Al-Shaibani, Ibrahim Saad Al-Bidah, Mohammed Saad Al-Bidah (Chelonian Research Foundation, 2022)
The objective of this research was to identify the variables that contribute to the scarcity of nurses in the workforce and examine their effects on nurses. Following the Cochrane library standards, a systematic search was conducted on five electronic databases (Research 4life—PubMed/Medline, Scopus, Embase, CINAHL) covering the period from 2010 to 2021. The remaining articles containing relevant information were compiled into a data extraction sheet for further thematic analysis. Four key themes were identified as contributing causes to the shortage of nurses in the workforce. These topics include obstacles related to policy and planning, hurdles to training and enrollment, factors that lead to nursing staff turnover, and the stress and burnout experienced by nurses. The worldwide shortage of nursing personnel is a complex issue that arises from several sources including individual, educational, organizational, managerial, and policy-making aspects. Keywords: nurse burnout, nurse retention, nursing shortage, nursing workforce, systematic review